An exploratory critique of the notion of social cohesion in contemporary South Africa - Desai, Ashwin (PINS-Psychology in Society, 2024)
This article seeks to situate the increasing salience of social cohesion in the context of the transition from apartheid to a post-apartheid society. It first part of the article focusses on the changing political and economic landscape post 1990. It pays particular attention to the role of Nelson Mandela as a symbol of national unity. While the fact that the African National Congress (ANC) government’s economic policies under his leadership failed to have a fundamental impact on levels of poverty and inequality, Mandela’s stature and ability to reach out to different constituencies created the conditions for him to be seen as a great unifier. His successors Thabo Mbeki and Jacob Zuma have also not had much success at the level of alleviating high levels of poverty and inequality while also not enjoying the same iconic status of Mandela. Starting in the Mbeki era but gaining momentum under the Zuma Presidency, the country has witnessed rising levels of community and labour unrest. In this context, the article argues that notions like social cohesion and ubuntu have assumed increasing importance as ways to stitch together a fracturing society. The latter part of the article argues that, with high levels of poverty and inequality, commodification of basic services and mounting social protests, it is difficult to deploy ideas like social cohesion, especially when new militant political subjectivities are challenging the hegemony of the ANC.